Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1006/dbio.2000.9955
|View full text |Cite
|
Sign up to set email alerts
|

TNF Signaling via the Ligand–Receptor Pair Ectodysplasin and Edar Controls the Function of Epithelial Signaling Centers and Is Regulated by Wnt and Activin during Tooth Organogenesis

Abstract: Ectodermal dysplasia syndromes affect the development of several organs, including hair, teeth, and glands. The recent cloning of two genes responsible for these syndromes has led to the identification of a novel TNF family ligand, ectodysplasin, and TNF receptor, edar. This has indicated a developmental regulatory role for TNFs for the first time. Our in situ hybridization analysis of the expression of ectodysplasin (encoded by the Tabby gene) and edar (encoded by the downless gene) during mouse too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
156
1
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(167 citation statements)
references
References 46 publications
(67 reference statements)
7
156
1
3
Order By: Relevance
“…The position of Troy-expressing cells in the enamel knot was indistinguishable from expression of Edar and Edaradd, but Troy was expressed at higher levels ( Fig. 1E,F ;Tucker et al, 2000;Headon et al, 2001;Laurikkala et al, 2001). Currently, the expression pattern of Xedar in tooth development is not known.…”
Section: Troy Expression During Tooth Developmentmentioning
confidence: 86%
See 2 more Smart Citations
“…The position of Troy-expressing cells in the enamel knot was indistinguishable from expression of Edar and Edaradd, but Troy was expressed at higher levels ( Fig. 1E,F ;Tucker et al, 2000;Headon et al, 2001;Laurikkala et al, 2001). Currently, the expression pattern of Xedar in tooth development is not known.…”
Section: Troy Expression During Tooth Developmentmentioning
confidence: 86%
“…Expression of Edar and Edaradd during tooth development have been described and linked to the primary enamel knots (Tucker et al, 2000;Headon et al, 2001;Laurikkala et al, 2001). Abnormal enamel knots have been found in Eda and Edar mutant mice (Pispa et al, 1999;Tucker et al, 2000;Laurikkala et al, 2001), although the defects in enamel knots are distinct with smaller enamel knots occurring in Eda mutant mice, whereas Edar mutant mice have extended lope-like enamel knots. Abnormal cusp formation have been found in Edaradd mutant mice, but the enamel knot phenotype has not been reported (Sofaer, 1969a(Sofaer, ,b, 1977(Sofaer, , 1979.…”
Section: Enamel Knot Gene Expression In Traf6 Mutant Molarsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro experiments have suggested that Eda is directly regulated by Wnt signaling in the tooth bud (Pengue et al, 1999;Laurikkala et al, 2001;Durmowicz et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Animal models have also suggested that the EDA/EDAR pathway regulates the development of ectodermal derivative. [21][22][23][24][25][26][27][28][29] It is also worth noting that, in studies on human population genetics, a strong signal of positive selection in Asian populations has been observed for the EDAR 370A allele. Specifically, the allele is rare in African and European populations and is associated with a long-ranged uniform haplotype in Asian populations.…”
Section: Introductionmentioning
confidence: 99%